Is it time to rethink ‘digital inequality’ (again)? - Sims, Christo (AoIR Selected Papers of Internet Research, 2013)
Digital inequality scholarship has rightly criticized the concept of the ‘digital divide’ for oversimplifying and distorting relations between digital media and social inequalities. Instead of focusing on binary conceptualizations of access, digital inequality scholars recommend studying ‘differentiated use,’ which depends on access, but which is mediated by additional factors such as skill. Despite these advances, much digital inequality scholarship retains many of the limitations of the digital divide framework it criticizes. As such, scholars thwart their honorable aims and paradoxically risk contributing to the reproduction of historical structures of power and privilege. This short paper identifies three persistent shortcomings with prevailing views about digital inequality: slippage between ‘digital inequalities’ and ‘social inequalities’; unacknowledged normativity; and a deficit model of difference. The paper ends with brief recommendations for how scholars and practitioners can move beyond these limitations.